Comparison of analog and digital patient decision aids for the treatment of depression: a scoping review - Sedlakova, Jana; Westermair, Anna Lisa; Biller-Andorno, Nikola; Meier, Christoph A.; Trachsel, Manuel (Frontiers in Digital Health, 2023)
Patient decision aids (PDAs) are important tools to empower patients and integrate their preferences and values in the decision-making process. Even though patients with mental health problems have a strong interest in being more involved in decision making about their treatment, research has mainly focused on PDAs for somatic conditions. In this scoping review, we focus on patients suffering from depression and the role of PDAs for this patient group. The review offers an overview of digital and Patient decision aids for depression 2 analog PDAs, their advantages and disadvantages as well as recommendations for further research and development. For this purpose, we narratively synthetized information extracted from 40 research articles. Our review revealed that there is more focus on digital PDAs in research than in clinical practice. Digitalization can enhance the benefits of PDAs by developing tools that are more efficient, interactive, and personalized. However, more research is needed regarding effective strategies for the implementation of digital PDAs into the clinical workflow, ethical issues raised by the digital format, and opportunities of tailoring PDAs for diverse patient groups.